Association between hypertension, oral microbiome and salivary nitric oxide: A case-control study - Barbadoro, Pamela; Ponzio, Elisa; Coccia, Erminia; Prospero, Emilia; Santarelli, Andrea; Rappelli, Giorgio G.L.; D'Errico, Marcello M. (Nitric oxide, 2021)
Nitric oxide (NO) produced in the oral cavity is a powerful resource for the human body, especially when NO-syntethase production is not adequate. The role of oral microbiome in determining blood pressure levels has been linked to the active role of some bacterial species involved in the nitro-reducing process. In the present study we investigated the correlation between selected oral microbiome characteristics, nitric oxide (NO) concentration in saliva and their association with hypertension. A case-control study including 48 (25 normotensive and 23 hypertensive subjects), subjects between 50 and 70 years old, was carried out at the dental clinic of an Italian teaching hospital. Characteristics of participants have been evaluated by means of a physical examination, and by an assisted interview. A real-time polymerase chain reaction in samples of saliva and plaque was used to detect Aggregatibacter actinomycetemcomitans, Prevotella intermedia, Tannerella forsythia, Porphyromonas gingivalis, Treponema denticola, Streptococcus mutans, Streptococcus sanguinis, Veillonella dispar and Neisseria subflava as well as total bacterial count. Nitric oxide in saliva was evaluated by the ELISA method. Normotensive subjects, compared with hypertensive subjects, had significantly higher concentration of NO (165.77 ± 61.7 vs 57.49 ± 19.61 μmol/l; p = 0.023), and higher bacterial concentration of the supragingival plaque (4.73E+07 ± 4.33+07 vs 4.02E+07 ± 4.00+07; p = 0.024). Bacterial species, usually associated to good oral health status, such as Neisseria subflava, were significantly more present in normotensive subjects than in hypertensive ones (9090.88 ± 5481.49 vs 4791.35 ± 4349.37; p < 0.001). considering the concentration of bacteria as a biomarker of the development of hypertension. The results support the association between hypertension, oral microbiome and salivary nitric oxide, in fact do the results allow us to establish any biomarkers (microbial or biochemical, NO) that allow early therapeutic intervention. •Appropriate dental care is an important factor in the prevention of non-communicable diseases.•Oral microbiome is confirmed to have an important role in developing a hypertensive disease.•Exist an association between salivary lower NO level and hypertension.•Specific microbiological differences are relevant between the oral flora of hypertensive, and normotensive people.